Does direct observation of antiretroviral therapy improve outcomes for HIV/AIDS patients compared to non-observed therapy?: A systematic review and meta-analysis of randomized-controlled trials - Ford, Nathan (Department of Public Health and Family Medicine, 2015)
Includes bibliographical references.